A STUDY ON INDICATIONS, MODE OF HYSTERECTOMY AND HISTOPATHOLOGICAL ANALYSIS OF HYSTERECTOMY SPECIMENS - K, LAKSHMI PRIYANKA; REDDY, KE MANGA; SRIVANI, TELLA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: To study the age distribution, indications, modes of hysterectomy, concurrent surgery done along with hysterectomy, and histopathological analysis of hysterectomized specimens. Methods: This study was conducted in the Department of Obstetrics and Gynecology, Mediciti Institute of Medical Sciences, a tertiary teaching hospital at Medchal. Medical records of 240 cases of hysterectomy performed from January 2015 to December 2021 were retrieved from the Medical Record Department. The age distribution, indications of hysterectomy, mode of hysterectomy, concurrent oophorectomy, and histopathological reports of hysterectomy specimens were analyzed in this study. Results: Out of the total 240 hysterectomies, 51.25% were in the age group of 40–49 years, followed by the age group of 50–59 years, i.e., 19.5%. Common indications for hysterectomy were AUB (36.25%), fibroids (34.58%), and UV prolapse (29.16%). Abdominal hysterectomy (62.5%) was performed more commonly than vaginal hysterectomy (29.16%). Histopathological analysis showed the most common pathologies as atrophic endometrium, leiomyoma in the myometrium, and inflammation in the cervix. Concurrent bilateral oophorectomy was done in 51.66%, unilateral oophorectomy was done in 10%, and ovaries were conserved in 38.33%. Conclusion: Hysterectomy is a common major gynecological surgery performed, most commonly in the perimenopausal age group. Although there is an increased trend toward the laparoscopic route, the abdominal route is still the preferred route. Leiomyoma is the most common pathology found in hysterectomized specimens. AUB being the most common indication for hysterectomy, there should be increased use of medical management, and patients should be counseled for conservative management in order to prevent increased surgical interventions.